Direct Patterning of a Carbon Nanotube Thin Layer on a Stretchable Substrate - Lee, Eunji; Kim, Hye Jin; Park, Yejin; Lee, Seungjun; Lee, Sae Youn; Ha, Taewon; Shin, Hyun-Joon; Kim, Youngbaek; Kim, Jinsik (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Solution-based direct patterning on an elastomer substrate with meniscus-dragging deposition (MDD) enables fabrication of very thin carbon nanotube (CNT) layers in the nanometer scale (80-330 nm). To fabricate the CNT pattern with CNT solution, contact angle, electrical variation, mechanical stress, and surface cracks of elastomer substrate were analyzed to identify the optimal conditions of O-2 treatment (treatment for 30 s with RF power of 50 W in O-2 atmosphere of 50 sccm) and mixture ratio between Ecoflex and polydimethylsiloxane (PDMS) (Ecoflex:PDMS = 5:1). The type of mask for patterning of the CNT layer was determined through quantitative analysis for sharpness and uniformity of the fabricated CNT pattern. Through these optimization processes, the CNT pattern was produced on the elastomer substrate with selected mask (30 mu m thick oriented polypropylene). The thickness of CNT pattern was also controlled to have hundreds nanometer and 500 mu m wide rectangular and circular shapes were demonstrated. Furthermore, the change in the current and resistance of the CNT layer according to the applied strain on the elastomer substrate was analyzed. Our results demonstrated the potential of the MDD method for direct CNT patterning with high uniformity and the possibility to fabricate a stretchable sensor.